(untitled) (Bhartiya Knowledge Systems, 2024)
Property rights of women is one of the neglected rights of women all over the world from ancient times. In India too though women were placed as Godesses mortal women were still traumatized in the name of property. In the name of property many women have lost their lives. However, the objectives of providing ‘stridhana’ was not to weaken her but to empower her. There were various ancient documents such as manusmirit,Naradasmirit,Yajnavalkyasmirit, Arthashastra where property rights of women were discussed.